Analisis Akuntansi Sustainabilitas Pada Bisnis Berkelanjutan Perumahan Syariah - Yopi Yudha Utama (ITB AAS INDONESIA Surakarta, 2021)
This study aims to understand sustainable business practices in sharia housing business using case study approach. The object of this research is DP, a sharia housing developer. The results show that the sharia housing developer has implemented sustainable aspects in its business. In the economic dimension, the company has fulfilled several aspects of both direct and indirect economic aspects. In the social dimension, several aspects of labor, human rights, and community indicators have been implemented. In the environmental dimension, aspects of product and service compliance, waste, water, and energy have been included by the company. In the dimension of spirituality, the activities undertaken by the company for its employees, housing residents, and the surrounding community have fulfilled the existing aspects. The results of this study indicate that the business practices of DP can creathe the concept of Tauhid sharia housing